Treatment for nausea and vomiting in pregnant women - Józef Muszyński; Jakub Brzozowski; Katarzyna Dettlaff (Polish Pharmaceutical Society, 2024)
Nausea and vomiting of pregnancy (NVP), associated as "morning sickness", is a problem faced by approximately 70% of pregnant women. The exact mechanism of NVP is not known, research suggests that growth and differentiation factor 15 (GDF 15) secreted by the placenta has a significant impact on these symptoms. Various scales and indices are used to describe the condition in NVP: the PUQE index, the Rhodes index, the McGill nausea questionnaire, and the visual-analogue scale. Depending on the severity of the disease course, therapy may include the non-pharmacological and/or pharmacological sphere. In this article, reports on the treatment of NVP worldwide, therapeutic preparations registered on the Polish market and current recommendations for their safety were presented. Non-pharmacological recommendations for NVP include a change in diet, avoidance of spicy foods, supplementation with preparations containing ginger rhizome or acupressure. Pyridoxine, antihistamines, dopamine D2 receptor antagonists, serotonin 5-HT₃ receptor antagonists and glucocorticosteroids are used to treat vomiting. Despite the wide range of antiemetics, there is still a search for effective NVP therapies, drugs with few side effects and, above all, adequate safety. Multicenter studies on a large population are particularly valuable in assessing teratogenicity, based on which are used to recommend whether a medicine can be used during pregnancy, especially in the first trimester. A two-component product containing pyridoxine and doxylamine was launched on the Polish market in December 2021. This drug was withdrawn from the US market in the 1980s because of suspicions that it was harmful. It is now recommended by both the US Food and Drug Administration and the Polish Society of Obstetricians and Gynaecologists as a first-line treatment for NVP. If treatment with this drug is ineffective, promethazine, in severe cases, metoclopramide and corticosteroids are also used in this indication. In some pregnant women, persistent vomiting leads to dehydration and malnutrition. In these cases, additional fluid therapy and clinical nutrition should be given.